KONSEP WASIAT DALAM PERSPETIF HUKUM ISLAM - Maimun, Maimun (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, Ekonomi Islam, 2017)
In Islam, the wasiyat is not merely a matter of property. In the  broadest  sense,  the  wasiyat  also  deals  with  moral messages  to  mankind.  In  the  Qur'an,  Allah  Almighty Himself  has  reminded  that  believers  always  have  a wasiyat in virtue and patience. This verse affirms that a person who is about to die must necessarily leave a wasiyat to his possessions, this verse may also serve as a legal basis (mandatory) of the wasiyat, particularly to the heirs whose liaison with the heir is cut off, become walled up caused by other  heirs,  such  as  the  case  of  a  grandchild  who  is wallowed  to  get  the  inheritance  of  the  datuk  (his grandfather)  due  to  his  uncle  (his  father's  siblings)  still exist.  The  will  for  the  non-heirs  required  to  fulfill  the maximum amount is 1/3 of the property left behind, after deducting the cost of holding the corpse and repayment of the debts. The law of wasiyat origin can not be more than 1/3  of  the  inheritance.  If  more  than  1/3  of  the  property, then  it  depends  on  the  heirs,  if  they  allow  it  can  be implemented, if not then carried out only related 1/3 of the treasure  alone,  Wasiyat  is  one  means  to  approach  Allah swt in order to get goodness in the world and the reward in  the  hereafter.  Wasiyat  is  also  a  means  to  provide assistance  to  people  in  need,  strengthening  friendships and  kinship  relations  that  are  not  his  heirs.  The  law  of wasiyat  when  examining  Surat  al-Baqarah  verse  180  is obligatory in accordance with the textual meaning of that verse.